Experimental and Numerical Acoustoelectric Investigation of the New SAW Structure with (RR)-P3HT Polymer in DMMP Detection - HEJCZYK, Tomasz Robert; WROTNIAK, Jarosław; MAGNUSKI, Mirosław; JAKUBIK, Wiesław (Archives of Acoustics, 2021)
This document presents the results of numerical analyses of the SAW gas sensor in the steady state. The effect of SAW velocity changes depending on how the surface electrical conductivity of the sensing layer is predicted. The conductivity of roughness sensing layer above the piezoelectric waveguide depends on the profile of the diffused gas molecule concentration inside the layer.Numerical results for the gas DMMP (CAS Number 756-79-6) for layer (RR)-P3HT in the steady state are shown. The main aim of the investigations was to study the thin film interaction with target gases in the SAW sensor configuration based on diffusion equation for polymers. Numerical results for profile concentration in steady state are shown.The results of numerical acoustoelectric analysis (NAA) allow to select the sensor design conditions, including the morphology of the sensor layer, its thickness, operating temperature and layer type. The numerical results based on the code written in Python, are described and analyzed. The theoretical results were verified and confirmed experimentally.